Genetic Correlation Analysis and Transcriptome-wide Association Study Suggest the Overlapped Genetic Mechanism between Gout and Attention-deficit Hyperactivity Disorder. (December 2021) - Kafle, Om Prakash; Wang, Xi; Cheng, Shiqiang; Ding, Miao; Li, Ping; Cheng, Bolun; Liang, Xiao; Liu, Li; Du, Yanan; Ma, Mei; Zhang, Lu; Zhao, Yan; et al.
Objectives: Gout is a common inflammatory arthritis, which is caused by hyperuricemia. Limited efforts have been paid to systematically explore the relationships between gout and common psychiatric disorders. Methods: Genome-wide association study summary data of gout were obtained from the GeneATLAS, which contained 452, 264 participants including 3, 528 gout cases. Linkage disequilibrium score regression (LDSC) was first conducted to evaluate the genetic relationships between gout and 5 common psychiatric disorders. Transcriptome-wide association studies (TWAS) was then conducted to explore the potential biological mechanism underlying the observed genetic correlation between gout and attention-deficit hyperactivity disorder (ADHD). The Database for Annotation, Visualization and Integrated Discovery online functional annotation system was applied for pathway enrichment analysis and gene ontology enrichment analysis. Results: LDSC analysis observed significant genetic correlation between gout and ADHD (genetic correlation coefficients = 0.29, standard error = 0.09 and P value = 0.0015). Further TWAS of gout identified 105 genes with P value < 0.05 in muscle skeleton and 228 genes with P value < 0.05 in blood. TWAS of ADHD also detected 300 genes with P value < 0.05 in blood. Further comparing the TWAS results identified 9 common candidate genes shared by gout and ADHD, such as CD300C ( P gout = 0.0040; P ADHD = 0.0226), KDM6B ( P gout = 0.0074; P ADHD = 0.0460), and BST1 ( P gout = 0.0349; P ADHD = 0.03560). Conclusion: We observed genetic correlation between gout and ADHD and identified multiple candidate genes for gout and ADHD.